Determinanty kulturowe zaburzeń odżywiania - Owsiejczyk, Aurelia (Wydawnictwo Naukowe UAM, 2007)
Eating disorders are complex conditions that arise from a variety of factors, including physical, psychological, cultural and social issues. This article presents a character of cultural factors, the influence of media images, which create its own definitions of beauty and attractiveness. A relative new phenomenon is a wave of pro-anorexic Web sites, where women and girls who indulge in anorexia nervosa attempt to glorify their chosen lifestyle. The author tries to present a cultural foundation of this problem and shows possible social consequences.
Cultural factors of eating disorders